2022
DOI: 10.1002/advs.202201494
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Branched Alkanes Feeds by a Synergistic Action of Zeolite and Metal‐Organic Framework

Abstract: Zeolites and metal‐organic frameworks (MOFs) are considered as “competitors” for new separation processes. The production of high‐quality gasoline is currently achieved through the total isomerization process that separates pentane and hexane isomers while not reaching the ultimate goal of a research octane number (RON) higher than 92. This work demonstrates how a synergistic action of the zeolite 5A and the MIL‐160(Al) MOF leads to a novel adsorptive process for octane upgrading of gasoline through an efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
(31 reference statements)
0
33
0
Order By: Relevance
“…The pore geometry is shown in Figure S1 of the Supporting Information and is best described as being a sequence of rectangular cavities (cuboids) that are rotated 90° to each other. Previous studies on isostructural MIL-160, [Al­(OH)­(furan-2,5-dicarboxylate)], revealed that this pore geometry causes highly efficient entropy-based separations of hexane isomers at room temperature . In contrast to MIL-160, CAU-10 has a larger pore sizewhich is commensurate with the length of short-chain alcoholsand a more pronounced internal hydrophobicityconfirmed by type V water adsorption isotherms with inflection points at relative pressure of 0.08 (MIL-160) or 0.18 (CAU-10) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore geometry is shown in Figure S1 of the Supporting Information and is best described as being a sequence of rectangular cavities (cuboids) that are rotated 90° to each other. Previous studies on isostructural MIL-160, [Al­(OH)­(furan-2,5-dicarboxylate)], revealed that this pore geometry causes highly efficient entropy-based separations of hexane isomers at room temperature . In contrast to MIL-160, CAU-10 has a larger pore sizewhich is commensurate with the length of short-chain alcoholsand a more pronounced internal hydrophobicityconfirmed by type V water adsorption isotherms with inflection points at relative pressure of 0.08 (MIL-160) or 0.18 (CAU-10) .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on isostructural MIL-160, [Al(OH)(furan-2,5-dicarboxylate)], revealed that this pore geometry causes highly efficient entropy-based separations of hexane isomers at room temperature. 10 In contrast to MIL-160, CAU-10 has a larger pore size�which is commensurate with the length of short-chain alcohols�and a more pronounced internal hydrophobicity�confirmed by type V water adsorption isotherms with inflection points at relative pressure of 0.08 (MIL-160) or 0.18 (CAU-10). 11 CAU-10 is thus a good candidate for studying the liquid phase separation of aqueous alcohol mixtures.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[ 4 ] Commonly, such mixtures are separated using adsorption methods, which consume low amounts of energy and are environmentally friendly. Numerous adsorbents, including metal–organic frameworks, [ 5 ] covalent organic frameworks, [ 6 ] MFI zeolite membranes, [ 7 ] and organic cages, [ 8 ] have been developed and investigated for the separation of small organic isomers, such as p‐xylene/o‐xylene, [ 9 ] 2‐methylpentane/3‐methylpentane, [ 10 ] 1‐bromopropane/2‐bromopropane, [ 11 ] and 1‐butane/2‐butane. [ 2c ] Despite exhibiting remarkable separation performance, most of these adsorbents lack the ability to recognize the entrapped isomer.…”
Section: Introductionmentioning
confidence: 99%
“…[4] As an alternative to energyintensive traditional separation methods such as distillation, extraction, etc., adsorptive separation using porous solid adsorbents such as silica gels, zeolites, activated carbons, and metal-organic frameworks (MOFs) represents a more energy-efficient technology. [5][6][7][8][9][10] The key to address this challenging task is acquiring robust and regenerable adsorbents with optimal separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the intensive efforts on porous materials have led to the emergence of metalorganic frameworks (MOFs) and covalent-organic frameworks (COFs) which surpass traditional zeolite materials for the separation of some important gaseous mixtures. [5][6][7][8][9][10] Unfortunately, MOFs and COFs, self-assembled through coordination and covalent bonding, respectively, are difficult to be regenerated when their frameworks are destroyed by heating or adsorbing moisture. In contrast, using noncovalent intermolecular interactions allows reversibility during assembly, giving rise to regenerable porous supramolecular self-assemblies (Fresh porous supramolecular materials can be readily recovered by recrystallization of the damaged materials).…”
Section: Introductionmentioning
confidence: 99%